Overview - de Carvalho, Marcelo R.; Craig, Matthew T. (Zootaxa, 2011)
At about this time last year, one of us (MRC) edited a manuscript submitted by systematic ichthyologists Randall D. Mooi and Anthony C. Gill to Zootaxa entitled “Phylogenies without synapomorphies—a crisis in fish systematics: time to show some character” (Mooi & Gill, 2010; hereafter M&G). A preview of this manuscript had been presented at an American Society of Ichthyologists and Herpetologists (ASIH) meeting in 2008, and caused quite a stir among many in attendance. The strong reaction was a response to what was perceived as unfair criticism of the molecular paradigm in the phylogeny of fishes, particularly of percomorphs, the core of their presentation. Before publishing M&G in Zootaxa, the authors were advised that a similarly strong reaction would probably occur. They did not flinch, and hence M&G was published (after peer review). Needless to say, M&G got strong feedback, either in a negative or positive vein, from molecular and morphological workers, respectively. MRC even received a critical e-mail from one molecular worker accusing M&G of superficiality and Zootaxa of employing “low” standards of scholarship.